Comparative assessment of Mini-FLOTAC, McMaster and semi-quantitative flotation for helminth egg examination in camel faeces - Khalid M. Mohammedsalih; Salma A. Hassan; Fathel-Rahman Juma; Shamsaldeen I. Saeed; Ahmed Bashar; Georg von Samson-Himmelstjerna; Jürgen Krücken (Parasites & Vectors)
Abstract Background Faecal egg counts (FECs) are essential for diagnosing helminth infections and guiding treatment decisions. For camels, no evaluations of coproscopic methods regarding precision, sensitivity and correlation between individual and pooled faecal samples are currently available. Methods Here, 410 camel faecal samples were collected in 2022 from South Darfur State, Sudan, and analysed to compare the semi-quantitative flotation, McMaster and Mini-FLOTAC methods in terms of precision, sensitivity, inter-rater reliability and helminth egg count correlations, as well as the effects of pooling samples. Six samples were used to assess precision for McMaster and Mini-FLOTAC, while the remaining 404 samples were evaluated for sensitivity, inter-rater reliability and egg count correlations. Of these, 80 samples were used in pooling experiments. Results Six analyses of each sample (n = 6) using the McMaster and Mini-FLOTAC methods revealed no significant difference in the coefficient of variation between the two. For strongyle eggs, 48.8%, 52.7% and 68.6% were positive for McMaster, semi-quantitative flotation and Mini-FLOTAC, respectively. The sensitivity of the three methods showed only minimal improvement when three egg counts were performed on the same sample. McMaster and Mini-FLOTAC had similar sensitivity for Strongyloides spp. (3.5% frequency), while it was lower for semi-quantitative flotation at 2.5%. Mini-FLOTAC was more sensitive for Moniezia spp., detecting 7.7% of positives compared with 4.5% for semi-quantitative flotation and 2.2% for McMaster. For Trichuris spp., frequencies were 0.3% with Mini-FLOTAC, 0.7% with McMaster and 1.7% with semi-quantitative flotation. Mini-FLOTAC also detected higher strongyle eggs per gram (EPG) of faeces (mean 537.4) compared with McMaster (330.1). More samples exceeded treatment thresholds with Mini-FLOTAC, with 28.5% of animals having EPG ≥ 200 compared with 19.3% for McMaster, while 19.1% showed EPG ≥ 500 with Mini-FLOTAC compared with 12.1% with McMaster. There was no significant correlation between individual and pooled strongyle FECs, as indicated by Pearson correlation coefficients of r ≥ 0.368 (P ≥ 0.113) and Spearman correlation. Conclusions Mini-FLOTAC outperformed semi-quantitative flotation and McMaster in diagnosing helminth infections in camels, offering greater sensitivity and detecting higher EPGs, particularly for strongyles, Strongyloides spp. and Moniezia spp. Thus, treatment decisions based on Mini-FLOTAC EPGs will lead to more treatments. Graphical Abstract